Respuesta :
we see this a geometric sequcne because each term is -6 times of the previous term
an=a1(r)^(n-1)
an=nth term
a1=first term
r=common ratio
n=which term
we see that it multiplies by -6 each time
and the first term is 1
so r=-6
a1=1
an=1(-6)^(n-1)
the explicit formula is
[tex]a_n=1(-6)^{n-1}[/tex]
and a5=1(-6)^(5-1)=1(-6)^4=1296
an=a1(r)^(n-1)
an=nth term
a1=first term
r=common ratio
n=which term
we see that it multiplies by -6 each time
and the first term is 1
so r=-6
a1=1
an=1(-6)^(n-1)
the explicit formula is
[tex]a_n=1(-6)^{n-1}[/tex]
and a5=1(-6)^(5-1)=1(-6)^4=1296